Breastfeeding technique and associated factors among lactating mothers visiting Gondar town health facilities, Northwest Ethiopia: observational method - Boko Loka Safayi; Nega Tezera Assimamaw; Destaye Guadie Kassie (BMC, 2021)
Abstract Background The breastfeeding technique is explained positioning, attachment, and suckling during breastfeeding. Ineffective breast feeding technique is one of the factors leading to premature discontinuation of breastfeeding and malnutrition. There is a limited study on the assessments of BFT and associated factors among lactating mothers in the study area. Therefore, the study aimed to assess breastfeeding technique and the associated factors among lactating mothers visiting Gondar town health facilities, Northwest Ethiopia. Methods An institution-based cross-sectional study was conducted from February 20 to March 20, 2020. An observational checklist and structured interviewer-administered questionnaire were applied to collect the data. The data were entered into Epi-Data 4.6 version and transferred to analyzed using SPSS version 20. Bi-variable and multivariable logistic regressions were performed to identify the association. The strength of association was identified using odds ratio with a 95% confidence interval (), and a p-value of 0.05 was declare as statistically significant. Results The proportion of effective BFT was 48% (95%, CI: 43.0-53.0%). The likelihood of applying proper BFT among age group of 18-20 years was 70% lower than (AOR = 0.3; 95% CI: 0.11-0.83) age group > 30 years. The odds of effective BFT in primipara mothers were 49% (AOR = 0.51; 95% CI: 0.32-0.82) lower compared to multiparous mothers. Likewise, the provability of effective BFT was 55% (AOR = 0.45; 95% CI: 0.29-0.70) times lower in women who had no counseling immediately after delivery compared to their counterparts. Moreover, effective breast feeding technique mothers who have breast problem was 78% lower than (AOR = 0.22; 95% CI: 0.07-0.68) mothers who have no breast problem. And mothers who had counselling of BFT during ANC follow up was 55% (AOR = 0.45; 95% CI: 0.29, 0.70) lower than mothers who had no counseling. Conclusion Just under half of the women in the study area applied proper breast feeding technique Younger and primipara mothers poorly performed to effective BFT. But women having counseling during antenatal care follow-up and immediately after delivery and not having breast problems applied BFT effectively. Hence, special emphasis have to give for younger and primipara mothers. Besides, educate the mother for preventing breast problems and working on enhancing counseling at postnatal clinic.